Study on the Validity of Marital Fidelity Agreement - Dong, Xuan (Journal of Theory and Practice of Social Science, 2023)
In recent years, with the continuous improvement of China's economic level and the increasing degree of social and cultural openness, the awareness of protection of personal rights and interests in marital relations has continued to rise, and the traditional view of marriage has been affected, and more and more couples choose to sign marital fidelity agreements in order to guard their marriage. However, the Civil Code and related interpretations are not clear how to adjust the spousal fidelity agreement, resulting in judicial practice on the validity of the spousal fidelity agreement "different judgment" phenomenon, the judicial credibility is affected. From the essence of marriage is a special "contract", the duty of fidelity between husband and wife both moral and legal nature. The spousal fidelity agreement both personal and property and different from the general civil contract, according to the type of responsibility agreed upon by the parties, the fidelity agreement should be divided into the fidelity agreement with the restriction of personal rights as the consideration, the fidelity agreement with the content of property division, mixed fidelity agreement, through the type of disposal to determine the effectiveness of the fidelity agreement, to protect the legitimate rights and interests of spouses, to play a disciplinary role for violations of the duty of fidelity and establish a healthy and civilized view of marriage and family.